STUDY LITERATURE REVIEW: PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM PENGAMBILAN KEPUTUSAN UNTUK MENGHADAPI TANTANGAN ABAD 21 - Zamarotul Azkiyah; Johanes Oenaimnou; Wisnu Ginto Silaban; Teguh Trianung; Supadi Supadi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
Times are constantly changing, and the world is entering the 21st century. The 21st century is marked by various rapid developments and changes that occur in human life and the universe. Changes and developments that really affect human life are technology and information. The influence of technology and information brings various positive impacts and on the other hand also brings negative impacts as well as various challenges that require humans to be ready to face them. The education sector also feels and experiences various challenges. To be able to deal with and overcome this, a leader who has adequate abilities and competencies is needed to be able to move members of educational institutions and make firm decisions in facing the challenges of the 21st century. The focus of this research is on transformational leadership styles in making decisions to face challenges in the 21st century. 21. Thus the research method used is a literature review study by analyzing several previous research articles and writings related to the research focus. The research objective is to analyze and understand the impact of transformational leadership on the role of decision-making in facing challenges in the 21st century.